OSMIUM BEHAVIOR IN ESTUARIES: THE LENA RIVER EXAMPLE - Levasseur S.; Rachold V.; Birck J.L.; Allègre C.J. (My University, 2000)
The behavior of dissolved osmium at the river/ocean interface was studied in the Lena River estuary. Dissolved osmium removal is observed at very low salinities. The loss is estimated to be 28% of the dissolved concentration of the river. The removal cannot be related to the flocculation of iron oxide–organic matter colloids, but occurs simultaneously with the loss of aluminum. The proposed mechanism is the adsorption of dissolved osmium on suspended particles in the maximum turbidity zone. If this is correct, then the removal of osmium in estuaries is probably a common phenomenon. No contribution of osmium from the sediments is detected but neither the samples nor the stratified nature of the estuary are favorable to the study of a flux from sediments. If this finding can be generalized, the estimated global riverine flux of osmium to the ocean has to be recalculated and the osmium residence time in the ocean would change from 3.3×104 yr to 4.6×104 yr.